Assessment of seed rate and weed management practice on weed control, crop productivity and profitability of dry direct-seeded rice - V.K. Choudhary; M.P. Sahu; R.P. Dubey; Rajbir Singh; J.S. Mishra (Journal of Agriculture and Food Research)
Dry direct-seeded rice (DDSR) is gaining attention as a sustainable alternative to traditional transplanted rice, addressing critical issues like water scarcity, labour shortage, and high production costs. However, heavy weed infestation poses a major limitation, significantly reducing yields. To evaluate optimal weed management and seeding rates, a field study was conducted during 2021 and 2022 at ICAR-Directorate of Weed Research, Jabalpur, India. The experiment tested four seed rates (30, 40, 50, and 100 kg ha−1) and four weed management practices {pendimethalin 38.7 % CS at 678 g a.i. ha−1 [2 days after sowing (DAS) as pre-emergence (PE)] followed by (fb) bispyribac-sodium 10 % SC at 25 g a.i. ha−1 [20 DAS, as post-emergence (PoE)], pretilachlor 30 % + pyrazosulfuron-ethyl 0.75 % WG 615 g a.i. ha−1 (PE) fb cyhalofop-butyl 5.1 % + penoxsulam 1.02 % OD 135 g a.i. ha−1 (PoE), pretilachlor 30 % + pyrazosulfuron-ethyl 0.75 % WG 615 g a.i. ha−1 (PE) fb hand weeding at 30 DAS and weedy check} on weed control, crop productivity and profitability. Results revealed that a seed rate of 100 kg ha−1 significantly suppressed weeds by 27.3–33.2 % due to higher plant density. Interestingly, the lowest seed rate (30 kg ha−1) led to better crop growth parameters, such as biomass, leaf area, and grain characteristics. Despite this, the highest grain yield (4641–5691 kg ha−1) and profitability (693–882 USD ha−1) were achieved at a moderate seed rate of 40 kg ha−1. Among weed management practices, the combination of pretilachlor + pyrazosulfuron-ethyl fb cyhalofop-butyl + penoxsulam proved most effective, with 90.8–96.7 % weed control efficiency, enhanced crop growth and grain yield (4612–5494 kg ha−1), and returns of 829–1089 USD ha−1. In conclusion, seeding at 40 kg ha−1 coupled with integrated herbicide application is the most effective strategy for maximizing weed suppression, crop productivity, and economic returns in DDSR systems.